2012
DOI: 10.1186/1751-0759-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception among patients with chest pain and palpitations before and after negative cardiac evaluation

Abstract: BackgroundPatients with chest pain or palpitations often have poor outcomes following a negative cardiac evaluation, with symptom persistence, limitations in everyday activities, and reduced health-related quality of life. The aims of this study were to evaluate illness perceptions before and after negative cardiac evaluations and measure the ability of a self-report questionnaire to predict outcomes.MethodsPatients (N = 138) referred for chest pain or palpitations to a cardiac outpatient clinic were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
0
20
3
5
Order By: Relevance
“…1a Rief et al [2008] und Schaefert et al [2012]). Es wird daher gefordert, Interventionen anzubieten, die auf ein besseres Verständnis und eine bessere persönliche Kontrolle der Beschwerden abzielen [Jonsbu et al, 2012] …”
Section: Anwendbarkeit Der Interventionergebnisse Der Analysenunclassified
See 2 more Smart Citations
“…1a Rief et al [2008] und Schaefert et al [2012]). Es wird daher gefordert, Interventionen anzubieten, die auf ein besseres Verständnis und eine bessere persönliche Kontrolle der Beschwerden abzielen [Jonsbu et al, 2012] …”
Section: Anwendbarkeit Der Interventionergebnisse Der Analysenunclassified
“…Bei Patienten mit nicht-kardialen Brustschmerzen bestehen bereits zum Zeitpunkt der diagnostischen Abklä-rung ungünstige Krankheitsrepräsentationen bezüglich der empfundenen Kontrollierbarkeit und des Verständnisses der Schmerzen. Diese schwächen die subjektiv erlebte Rückver-sichertheit nach Mitteilung unauffälliger kardialer Befunde deutlich ab und beeinflussen so den Verlauf der Beschwerden sowie assoziierte psychosoziale Beeinträchtigungen ungünstig [Donkin et al, 2006;Jonsbu et al, 2012;Robertson et al, 2008]. Die einfache ärztliche Rückmeldung über unauffällige Untersuchungsbefunde reicht dann häufig nicht aus, um die Sorgen und Ängste der Patienten langfristig zu beseitigen [Jonsbu et al, 2012;Robertson et al, 2008].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Patients with NCCP perceive themselves as having less control over their situation and less understanding for their chest pain compared to patients with cardiac pain, despite having undergone a cardiac evaluation (55,59). They experience unfulfilled information needs, including unanswered questions and healthcare providers not focusing on their individual problems (60).…”
Section: The Impact Of Non-cardiac Chest Painmentioning
confidence: 99%
“…Relatively recent studies have shown that negative illness perception is associated with psychological distress and chest pain (22,59,144), and that the way patients perceive and interpret their chest pain has an impact on the management of NCCP (82). Fear of cardiac sensations may increase pain, disability and avoidance behaviour (81).…”
Section: Psychological Distress Healthcare Utilization and Societal mentioning
confidence: 99%